2019
DOI: 10.1108/ijmce-04-2018-0016
|View full text |Cite
|
Sign up to set email alerts
|

Peer coaching in a school in Cairo, Egypt

Abstract: Purpose The purpose of this paper is to examine how peer coaching was introduced in one school in Egypt and to identify barriers and opportunities for successful implementation. Design/methodology/approach The methodology included semi-structured interviews with eight teachers, participant observation of their classes and meetings, and three focus group meetings with teachers and school administrators. Findings Ladyshewsky’s (2017) five key aspects of peer coaching are considered in the findings: establish… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 25 publications
1
3
0
Order By: Relevance
“…First, RPO's positive impact on collaborative school culture can be explained because RPO enables the creation of collaborative professional relationships in practice, that is, progressing from a collaborative discourse to a collaborative action, and thus promoting schools in which educators work together and learn from one another, sharing goals and values about teaching to meet the school educational challenges (Corcelles‐Seuba et al., 2022; O'Leary & Savage, 2020). Using the validated TCPQ instrument and a pre/post research design, our research contributes to reinforcing previous results obtained from qualitative studies that reported an increase in teachers' collegiality after RPO intervention (Arnau et al., 2004; Hamilton, 2013; Motallebzadeh et al., 2017; Rosselló & de la Iglesia, 2021; Sider, 2019; Slater & Simmons, 2001). Therefore, RPO can potentially serve as a mechanism to establish more supportive and trusting collaborative relationships between peers and promote professional learning communities' development (Darling‐Hammond et al., 2017; Hargreaves & O'Connor, 2018).…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…First, RPO's positive impact on collaborative school culture can be explained because RPO enables the creation of collaborative professional relationships in practice, that is, progressing from a collaborative discourse to a collaborative action, and thus promoting schools in which educators work together and learn from one another, sharing goals and values about teaching to meet the school educational challenges (Corcelles‐Seuba et al., 2022; O'Leary & Savage, 2020). Using the validated TCPQ instrument and a pre/post research design, our research contributes to reinforcing previous results obtained from qualitative studies that reported an increase in teachers' collegiality after RPO intervention (Arnau et al., 2004; Hamilton, 2013; Motallebzadeh et al., 2017; Rosselló & de la Iglesia, 2021; Sider, 2019; Slater & Simmons, 2001). Therefore, RPO can potentially serve as a mechanism to establish more supportive and trusting collaborative relationships between peers and promote professional learning communities' development (Darling‐Hammond et al., 2017; Hargreaves & O'Connor, 2018).…”
Section: Discussionsupporting
confidence: 76%
“…Teachers were asked to voluntarily participate in the RPO process as part of their training and professional development programme. It was essential to ensure voluntary participation and data confidentiality to promote a secure environment for peer learning (Hammersley‐Fletcher & Orsmond, 2005; O'Leary & Savage, 2020; Sider, 2019). Participants were asked to choose a pair from their school for the RPO process following the symmetry criteria in experience and status.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although this is recognized as an important aspect of mentoring, it is reported that in many contexts the mentor will dominate such interactions, with both the mentor and trainee accepting this as appropriate (Hudson, 2014). One way to counteract this, as Sider (2019 Wyre) discusses in the context of Egypt, is to use peer–tutors where the relationship is more easily perceived as non-hierarchical.…”
Section: Literature Reviewmentioning
confidence: 99%